Growing Body Disrelish among Teenage Girls: A Serious Health Issue: Cross-sectional Study Based on College Girls of Ernakulam District - Bincy Mole Baby, Dr Balakrishnan Kalamullathil (International Journal of Advanced Science and Technology, 2020)
Background: Self-perception identifies with how individuals ponder their very own body. In the present society, with the developing feeling of perfect self-perception, youths attempt to lose or put on body weight to achieve that ideal body. Objectives: To study the phenomenon of body disrelish among teenage girls. Identify the major causes of this growing disaster. To check out the weight control measures adopted by college girls. And finally to analyze the physical, mental impact caused due to this growing epidemic. Methodology: A cross-sectional study was done among 1000 college girls from five colleges in Ernakulum district. A semi-organized survey was utilized to gather information on different variables related with self-perception disappointment and health issues associated with it. Weight list (BMI) of the members was also determined. Results: Self-recognition disillusionment was there among 80.2% of the youngsters. It was found that segments, for instance, higher BMI, socio cultural strain to be thin and sadness were all basically associated with self-observation frustration. The most normally used weight control measures were eating little meals and skipping dinners. Enhancing the appearance and body shape were the essential clarifications behind weight control rehearses.